The Role Of Brand Image As Mediating Variable In The Influence Of Price And Promotion On Buying Interest (Study Case On Hyundai Electric Car) - Soegeng Wahyoedi; Saparso; Miki Effendi (International Journal of Science, Technology & Management, 2021)
The development of environmentally friendly vehicles is currently a global trend among car manufacturers. This is in addition to being triggered by regulations from countries that have committed in the 2016 Paris agreement to reduce greenhouse gas emissions and save fossil-based fuels that will run out, considering that fossil fuels are a type of non-renewable natural resource. For this reason, the global automotive industry has begun to produce electric cars, which are referred to as renewable energy sources, and to reduce carbon emissions. Because this electric car is a new product, researchers are interested in knowing how someone is buying an electric car. One of the elements that influence a person's buying interest is the price. Besides the price, buying interest is also influenced by promotion. With the proper promotion, it can encourage people to buy. Therefore, this study wanted to examine the effect of price and promotion on buying interest mediated by brand image. Sampling using non-probability sampling and purposive sampling with criteria for the general public living in Jabodetabek who already have a car and can buy a car. Data analysis in this study used a Structural Equation Modeling (SEM) approach based on Partial Least Square. This study found that price, promotion, and brand image had a significant and positive effect on buying interest. Brand image mediates significantly and positively the relationship between price and promotion on purchase intention.